Penggunaan Lembar Kerja Digital untuk Mengembangkan Keterampilan Komunikasi Mahasiswa pada Mata kuliah Telaah Kurikulum Fisika - Hikmawati, Hikmawati; Ayub, Syahrial (Mataram University, 2021)
This study aims to develop students' communication skills in the Physics Curriculum Study course through the use of Digital Worksheets. The subjects of this study were 23 students of class 5B. The student came from the Physics Education Study Program, University of Mataram, who attended the Physics Curriculum Study course in the odd semester of the 2021/2022 academic year. The research instrument used was a student communication skill observation sheet with three indicators. Observations were made online at the Learning Management System (LMS) equipped with Digital Worksheets on the Discussion Forum menu. Observations were made every meeting, namely 14 times using a 4-scale rating score. The increase in score from the first meeting to the last meeting was calculated using N-gain. The average score of student communication skills is 79.5 which is in good criteria. The improvement of students' communication skills based on the calculation of N-gain is 72.7 which is in the high category. Thus, the use of Digital Worksheets can develop students' communication skills in the Physics Curriculum Study course.